(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Infection control and knowledge of common "infectious diseases" is essential for safe dental practice. Conveyance of infectious diseases is likely "from one individual to another during dental procedures", thorough" blood-borne" viruses and bacteria "such as hepatitis" , human immunodeficiency virus (HIV). Thence in dental practice, the sterilization and particular protection is of most importance Process in dental procedures, and patient sponsor settings seek specific strategies guide to prevent the transmission of diseases among dental students , oral verdure care staffs and their patients. Aim: Current study highlight the methods and behavior to evaluate the benefits of awareness, stance and pursuit of infection control between dental students in training dental clinic at Babylon dental collage . Materials and Methods: A cross-sectional wipe using a rear ordered questionnaire was executed. The reconnaissance consisted of 38 closed-ended questions that included the key areas of infection control, including hand hygiene, personal preservation, sterilization and disinfection and ecological infection monitoring. There were also questions to elicit perceptions regarding the treatment of HBV and HIV/AIDS patients. Results: Survey study was done for dental students replied to the reconnaissance. Their situation and realization across infection control in college teaching clinic .The results were assorted between 100% were orderly using gloves and 96% mask with patient to 6% were orderly wore eye glasses. The type of sterilization of instrument was 90% autoclave and 10% oven and from analysis of data revealed most teaching clinics devoid of instruction post about control of infection control measures Conclusion: "Improved compliance with recommended infection control procedures is required for all dentists" and graduated dental students predestined in the existing project. Enduring instruction "programs and short-time" processions about "cross-infection and infection control" modes are convenient to progress the awareness and attitude of Dental students in infection control.